2011
DOI: 10.1007/s00038-011-0271-7
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ intentions to accept human papillomavirus vaccination for sons and daughters: exploratory findings from rural Honduras

Abstract: Few Honduran fathers were aware of HPV or HPV vaccination, but after receiving information, most would accept HPV vaccination for their sons and daughters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 37 publications
3
13
1
Order By: Relevance
“…Compared to one Honduran study (Perkins et al, 2012) and one German study (Kuznetsov et al, 2012) where 22% and 29% of fathers, respectively, had heard of HPV, awareness in this study was slightly higher at 37%, but considerably lower than a recent Italian study where 77% of fathers had heard of HPV (Pelucchi et al, 2010). Higher education level in the Italian study is suggested to be one of the reasons for the difference.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Compared to one Honduran study (Perkins et al, 2012) and one German study (Kuznetsov et al, 2012) where 22% and 29% of fathers, respectively, had heard of HPV, awareness in this study was slightly higher at 37%, but considerably lower than a recent Italian study where 77% of fathers had heard of HPV (Pelucchi et al, 2010). Higher education level in the Italian study is suggested to be one of the reasons for the difference.…”
Section: Discussioncontrasting
confidence: 84%
“…It was also similar to fathers in Honduras (94%) (Perkins et al, 2012) and considerably higher (65%) than the Italian study (Pelucchi et al, 2010), indicating that father's awareness of HPV is not a measure of HPV vaccine acceptance. While all single fathers in both the present and Honduran study indicated they would vaccinate their daughter against HPV, our study did highlight some issues specific to these fathers, such as talking about the sexual nature of HPV or place of vaccination, that need to be addressed.…”
Section: Discussionsupporting
confidence: 51%
“…Similarly, 24.6 -68% of women were found to wish vaccination for their daughters in studies conducted in Turkey (Onan et al, 2009;Dursun et al, 2009). In the literature, the rates of for mothers' willingness to have their daughters vaccinated against HPV vary between between 70% and 88% (Fazekas et al, 2008;Watts et al, 2009;DiAngi et al, 2011) and that for fathers to be between 90% and-94% (Pelucchi et al, 2010;Perkins et al, 2012). However, there are also studies indicating lower (Dempsey et al, 2009) and higher rates (Pelucchi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in populations like Turkey in which the family concept is important, the values of family members are considered to be affected by each other. Despite the fact that there is no similar study in the literature evaluating the decision for vaccination between mothers and daughters, there are studies indicating that there is consistency between the mothers and fathers in terms of opinions on vaccination (Breitkopf et al, 2009;Perkins et al, 2012). Breitkopf et al (2009) reported that 91% of parents of whom all were healthcare personnel believed that their and their partners' decisions would be similar, and 77% believed that their decisions and decisions of their daughters would be similar (Breitkopf et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…
We read the paper by Perkins et al (2011) with great interest because it highlighted a very important issue about fathers' attitudes towards HPV infection and their intentions regarding HPV vaccine. No surveys have been published yet demonstrating the extent of fathers' knowledge of HPV and HPV vaccine together with its acceptance in Germany.
…”
mentioning
confidence: 99%